Meta Analisis: Beberapa Variabel yang Memengaruhi Earnings Response Coefficient (ERC) - Cindy Limtaroli; Venny -; Novita -; Carmel Meiden (Universitas Malahayati, 2023)
An increase in the number of capital market investors indicates an increasing need for financial information, especially earnings information in which its quality can be measured through earning response coefficient (ERC). The objective of this study is to integrate the factors that affect the earnings response coefficient. This research was carried out using the meta analysis method. The sampling technique used in this research is the purposive sampling method and the object of research is journal articles with topics of earnings response coefficient with a research period ranging from 2009-2020, which resulted in 30 samples obtained. The integration results show the disclosure of corporate social responsibility, company size, profitability, leverage and company growth have a significant effect on the earnings response coefficient.